Protection of intellectual property rights an Indian perspective - Balamurugan, R.; Radhakrisnan, R. (Universiti Utara Malaysia, 2010)
The objective of this paper is to provide an overview of the Indian Innovation System, IPR system and other related activities such as Judicial System, Enforcement System, and Academic Institutions etc. The paper is based on the existing data and relates those data and results to the India’s Intellectual Property Rights System, Innovation, Research and Development. This paper focus on the recent reforms in IPR laws to achieve a legal framework for protecting IPR that is comparable to that of most developed nations. As a part Information Technology, three major IT organizations focus on innovation and research discussed in addition to an overview about major multinational companies’ research initiatives in India.